The geometry of the generalized algebraic Riccati equation and of the singular Hamiltonian system - Ntogramatzidis, Lorenzo; Ferrante, A. (Taylor & Francis, 2019)
This paper analyses the properties of the solutions of the generalized continuous algebraic Riccati equation from a geometric perspective. This analysis reveals the presence of a subspace that may provide an appropriate degree of freedom to stabilize the system in the related optimal control problem even in cases where the Riccati equation does not admit a stabilizing solution.